Mexico : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
The staff report on Mexico's 2008 Article IV Consultation focuses on economic and financial sector implications of the global crisis. Inflation has been anchored in a low range, and public and private balance sheets have been substantially strengthened. Most importantly, public external debt and financing requirements have been sharply reduced. The external current account position has been solid, and official reserves have been built up steadily, though not to the extent in some other emerging markets. The banking system is highly profitable and well capitalized.